Innate-like NKp30+CD8+ T cells armed with TCR/CAR target tumor heterogeneity - Margareta P. Correia; Ana Stojanovic; Winfried S. Wels; Adelheid Cerwenka (OncoImmunology, 2021)
Intratumoral heterogeneity is frequently associated with tumor immune escape, with MHC-class I and antigen expression loss rendering tumor cells invisible to T cell killing, representing a major challenge for the design of successful adoptive transfer protocols for cancer immunotherapy. While CD8+ T cell recognition of tumor cells is based on the detection of MHC-peptide complexes via specific T cell receptors (TCRs), Natural Killer (NK) cells detect tumor-associated NK ligands by an array of NK receptors. We have recently identified a population of innate-like CD8+ T cells marked by the expression of NKp30, a potent natural cytotoxicity activating NK receptor, whose tumor ligand, B7H6, is frequently upregulated on several cancer types. Here, we harnessed the dual-recognition potential of NKp30+CD8+ T cells, by arming these cells with TCRs or chimeric antigen receptors (CARs) targeting Epidermal Growth Factor Receptor 2 (ErbB2, or HER2), a tumor-associated target overexpressed in several malignancies. HER2-specific NKp30+CD8+ T cells killed not only HER2-expressing target cell lines, but also eliminated tumor cells in the absence of MHC-class I or antigen expression, making them especially effective in eliminating heterogeneous tumor cell populations. Our results show that NKp30+CD8+ T cells equipped with a specific TCR or CAR display a dual capacity to recognize and kill target cells, combining the anti-tumor activity of both CD8+ T and NK cells. This dual-recognition capacity allows these effector cells to target tumor heterogeneity, thus improving therapeutic strategies against tumor escape.